PERBANDINGAN EFEKTIFITAS ORAL HYGIENE MENGGUNAKAN ENZYM LACTOPEROXIDASE DENGAN CHLORHEXIDINE DALAM PENCEGAHAN VAP DI ICU RS X - Agus purnama; Raushan Fikri (Jurnal Surya Muda, 2020)
Various types of infections can occur in patients who experience care in a ward, such as nosocomial infections or what is now more commonly known as Healthcare Associated Infections (HAI's). Nosocomial infection is an infection that patients get from the hospital when the patient is undergoing a nursing care process. hospital-acquired infections occurred to patients that treated for 72 hours and these patients do not show signs and symptoms of infection at the time of admission to the hospital. Ventilator Aquired Pneumonia (VAP) is a type of nosocomial infection in patients who have a general ventilator after 48 hours from the start of the installation of a mechanical ventilator. Data obtained from the Infection Control and Prevention Control Unit (PPI) in September 2018 Surgery Area Infection (SAI) 0.16%, Hospital Aquired Pneumonia (HAP) 1.4%, Ventilator Aquired Pneumonia (VAP) 2.8%. VAP occurs due to microorganism infections such as Pseudomonas aeruginosa, Klebsiella pneumoniae, and Enterobacter as a result of the installation of ETT tubes that become the pathogen entry into the lungs. The antibacterial mouthwash are mainly determined by the active ingredients contained in it such as Chlorhexidine and Enzym Lactoperoxidase. The purpose of this study was to compare the effectiveness of oral hygiene using the enzyme lactoperoxidase with chlorhexidine in the prevention of vap. Type of this research is a quasi-experimental study with a pretest-posttest control group research design. The data used in this study are primary data with data collection using CPIS observation sheets. In general, the CPIS sheet contains 6 diagnostic parameters for VAP. The hypothesis test uses the Independent T Test method. The results showed that there was no significant difference between oral hygiene using Lactoperoxide and Chlorhexidine in the prevention of VAP p = 0.290 (p> alpha 0.05)